Five go off in a caravan - "Blyton, Enid" (London; Hodder Children's, 2010)
A caravan holiday for The Famous Five is bound to be an adventure! When they stumble across a circus troupe, Julian, Dick, Anne, George and even Timmy the dog are thrilled. But some of the circus people have more sinister plans than just clowning around ..
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Action and adventure fiction